The dark side of mental toughness: a meta-analysis of the relationship between the dark triad traits and mental toughness - Liang, Taihe; Wang, Xianfei; Ng, Sanfan; Xu, Xuefeng; Ning, Ziheng (Frontiers in Psychology, 2024)
Introduction This meta-analysis investigates the relationships between the Dark Triad personality traits (narcissism, Machiavellianism, and psychopathy) and mental toughness. Previous research has shown mixed results regarding the influence of these traits on mental toughness. The objective of this meta-analysis is to synthesize existing literature and provide a comprehensive understanding of how Dark Triad traits correlate with mental toughness. Methods A comprehensive literature search was conducted in 7 databases, Data were extracted by correlation and analyzed using a random-effects model. Results The results yielding 27 effect sizes with a total of 12,378 participants, revealed a significant moderate positive association between narcissism and mental toughness (r = 0.327, p < 0.001), suggesting that individuals with higher levels of narcissism tend to exhibit greater mental toughness. However, no significant associations were found between Machiavellianism (r = 0.023, p = 0.719) or psychopathy (r = −0.022, p = 0.625) and mental toughness. Discussion The findings contribute to a more nuanced understanding of the Dark Triad traits and their differential associations with adaptive psychological constructs, highlighting the unique role of narcissism in mental toughness. This meta-analysis provides valuable insights for future research and practical applications in fostering adaptive aspects of narcissism while mitigating its potential maladaptive consequences.